A educomunicação e a formação de professores: o papel do programa Imprensa Jovem na construção da formação crítico colaborativa - Sousa, Sandra Santella de (2019)
This research aims to critically understand how the teacher education programs as continuous development happen in the Program called “Imprensa Jovem” (Young Press) of the São Paulo city Education Bureau, examined under the critic collaborative process. For this reason, it has the following specific objectives: a) to describe the sort of education that happened; b) analyze if it happened and, if so, how this development allows critic-collaborative development in the teachers; c) evaluate the kind of Agency that the teachers have developed under this process. This study is based on the core concepts of Educommunication (planning, application and development of communicative practices in school; critic reading of communication media; enlargement of people’s expression abilities) by the Social Cultural Historical Activity theory and the concept of Agency. It uses the methodology called Critical Collaborative Research, in which participants and researcher act together, reflecting critically aiming the elaboration of new possibilities for their activity. Data analysis had as a parameter the actions of reflexive critic: to describe, to inform, to confront and to rebuild; and also benefited from the categories of enunciation, linguistics and discourse in an argumentative analysis. Data discussion points to the importance of the critic collaborative process in loco during the teacher education, as it indicates that the dialogue between theory and practice is crucial for new meanings of school pedagogical activities